1987
DOI: 10.1152/jappl.1987.62.2.464
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic, iron-related, and acute-phase protein responses to sustained strenuous exercise

Abstract: This study was undertaken to gain insight into the mechanisms responsible for the hypoferremia occurring after severe exercise. To this end, 18 athletes who were competing in a 160-km triathlon involving canoeing, cycling, and running were evaluated before the race, immediately after the finish, and thereafter at 30 min, 24 h, and 48 h. The evaluation included plasma iron, total iron-binding capacity, lactoferrin, ferritin, haptoglobin, cortisol, various enzymes, and white cell count. The cortisol, white cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
1
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(61 citation statements)
references
References 0 publications
9
50
1
1
Order By: Relevance
“…Although elevated resting levels of CRP were shown in this study and have been shown elsewhere, 14,27 more studies seem to be revealing that athletes exhibit a chronic training/exercise-induced reduction in resting CRP concentrations. 17,22,29 Whether these suppressed resting levels of CRP increase an individual's susceptibility to infection remains to be investigated.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Although elevated resting levels of CRP were shown in this study and have been shown elsewhere, 14,27 more studies seem to be revealing that athletes exhibit a chronic training/exercise-induced reduction in resting CRP concentrations. 17,22,29 Whether these suppressed resting levels of CRP increase an individual's susceptibility to infection remains to be investigated.…”
Section: Discussionsupporting
confidence: 44%
“…Whilst numerous studies have shown the APP C-reactive protein (CRP) to be significantly elevated following exercise, 18,21,26,27 there still remain a large number of acute phase reactants that have not been thoroughly investigated. Therefore, the aims of this study were firstly to confirm the reported increases in CRP following a prolonged, strenuous bout of exercise, and secondly to monitor alterations in less researched acute phase reactants, up to 3 days after an ultramarathon.…”
Section: Introductionmentioning
confidence: 99%
“…Acute muscle injury resulting from strenuous exercise 21 or myocardial infarction 22 has been shown to initiate the acute phase response. Based on similarities with malignant hyperthermia, it has been proposed that patients with neuroleptic malignant syndrome may have abnormal calcium channels in skeletal muscle.…”
Section: Muscle Breakdownmentioning
confidence: 99%
“…Human plasma collected immediately (1 hr) after exercise was injected intraperitoneally into rats, causing a significant elevation of core temperature in those animals (Cannon & Kluger, 1983). Taylor et al (1987) also sampled volunteers from a triathlon event involving canoeing, cycling, and running. Data showed exercise training was associated with induction of acute-phase reaction as evidenced by a decrease in serum iron concentration and an increase in C-reactive protein.…”
Section: Long-term Exercise Training Selectively Alters Serum Cytokinmentioning
confidence: 99%